Faktor Risiko Penyakit Diabetes Mellitus pada Tenaga Kesehatan di Puskesmas Wilayah Lampung Utara - Taufiq, Ihsan; Sono (Jurnal Kesehatan, 2024)
The incidence of non-communicable diseases, especially diabetes mellitus (DM), continues to increase. This condition will have a negative impact on people's health status. Diabetes mellitus that persists for a long time will cause complications that can increase medical costs and reduce the quality of life of diabetes sufferers. There are risk factors that can be known to avoid DM. Health workers at Community Health Centers are expected to be role models in early detection of DM. The research was carried out from September to November 2023 to identify risk factors in health workers at the North Lampung Regional Health Center. The research design was descriptive, with 301 respondents consisting of 16 doctors, 109 nurses, and 176 midwives at 16 community health centers. The measuring tool uses the CANRISK questionnaire. Respondents were interviewed and measured/performed physical examinations related to risk factors for DM, including measuring height and weight, abdominal circumference, and instant blood glucose levels. The measurement results were processed in univariate analysis with the following results: The level of risk factors among health workers in the North Lampung Community Health Center who had high risk was 7 people (2.33%), moderate risk was 40 people (13.29%) and low risk was 254 people (84.39%). For this reason, health workers must change risk factors that can be modified, including BMI, waist circumference, physical activity, consumption of vegetables and fruit, blood pressure, and blood glucose.